(untitled) (مجلة المنصور, 2022)
The current study deals with the use of MRP II in planning for graduate study in Department of Economics, College of Administration and Economics, al-Mustansiriyah University. This study aims at studying the possibility of qualifying the Systems of Planning and Control over Production for functioning in the Higher Education sector; and the ability of benefiting from the reports submitted by these systems in making decisions relevant to the best utilization of the available resources. Such decisions may include determining the proper number of students who may be seated by the aforesaid department. When preparing the reports of MRP II, statistical techniques and percentages were used to utilize classrooms, laboratories, and teaching staff capacities. The most significant conclusion of the study is the ability to employing MRP II system in the field of higher education; and the inability to generalize bill of materials (bachelor degree in economics) over the other departments of the college, or the other economics departments in other universities, because bill of materials varies according to the educational system being used in the relevant college, the curriculum, and other variable factors. The most significant recommendations, however, are represented by conducting more studies relevant to applying other systems of planning and control in the educational institutions, such as the system of Enterprise Resources Planning (ERP), so as to enhance the accuracy of the planning process in these institutions.